Climate Change Mitigation Strategies and Media Exposure to Sustainability Report Publications : an Empirical Study of Mineral Mining Companies for the 2020–2024 Period - Dinda Lestari; Lukita Tripermata; Lesi Hartati (Economics and Digital Business Review, 2026)
This study aims to examine the effect of climate change mitigation strategies and media exposure on the publication of sustainability reports in mineral mining companies listed on the Indonesia Stock Exchange during the 2020–2024 period. This research employs a quantitative approach using secondary data obtained from annual reports, sustainability reports, and official company websites. The sample was selected using a purposive sampling method. Data analysis was conducted using multiple linear regression to test both partial and simultaneous effects. The results are expected to provide insight into the role of climate change mitigation strategies and media exposure in enhancing sustainability report publication among mineral mining companies in Indonesia